Designing a Pattern of Relationship between the Functions of the Intermediary Institutions of Open Innovation in Health System - Mohammad Salmani; Nasser Feghhi Farahmand; Yaghoob Alavi Matin; Reza Khodaie Mahmoudi (Taṣvīr-i salāmat, 2022)
Background. The health system generally comprises a variety of players. In the health system, there are intermediary institutions of innovation, playing a key role in reducing the distance between the members of the network and building trust among them. Therefore, this study aimed to develop a pattern of relationship between the function of the intermediary institutions of open innovation in the health system. Methods. This descriptive-analytical study was conducted in two main phases. The first phase was carried out to identify and approve the principal components of the function of the intermediary institutions in the health. The data were collected based on a researcher-made questionnaire in accordance with the existing research literature. The questionnaire was distributed among 140 managers and experts of the research and quality improvement divisions of the clinical centers, laboratories, and pharmaceutical companies. The data were analyzed using confirmatory factor analysis (CFA). In the second phase, interpretive structural modeling (ISM) was employed to design the pattern of relationship. The views of 12 experts were used for designing the pattern. ISM was used for developing various parts of the questionnaire. Results. The CFA findings indicated the proper relationship between the principal components and the respective indicators. Accordingly, all principal components of the pattern of the functions of the intermediary institutions were confirmed in the statistical population. Based on the ISM, the findings revealed that components of "organizing and supplying resources" and "strengthening the network and participation" were the most effective functions of the intermediary institutions. Moreover, the component of commercialization was the most susceptible function of the intermediary institutions. Conclusion. The intermediary institutions can reduce the deficits in each stage of the process of innovation in the field of health according to their various functions, serving as an accelerator increasing the knowledge and innovation in the field of health.